EFEKTIVITAS PATCH SEDERHANA DARI EKSTRAK DAUN KAYU JAWA (Lannea coromandelica (Houtt.) Merr.) TERHADAP PENYEMBUHAN LUKA SAYAT PADA TIKUS (Rattus norvegicus) - Azzahrah, Nur Faatimah; Jamaluddin, Abdul Wahid; Adikurniawan, Yuko Mulyono (Jurnal Ilmiah As-Syifaa, 2019)
Kayu jawa plants are one type of traditional plant that is often used to treat wounds, both internal and external wounds. This plant has been shown to have anti-microbial, anti-oxidant and anti-inflammatory effects. Flavonoid compounds have anti-inflammatory activity by protecting erythrocyte membranes against membrane damage causing hemolysis because flavonoids can inhibit inflammatory mediators and free radicals. This study aims to determine the effect of the administration of simple patch from Kayu Jawa leaves extract (Lannea coromandelica Houtt. (Merr.)) On wound healing in white rats (Rattus norvegicus) by looking at the extent of the wound closure and changes in wound morphology compared to controls. This study used a laboratory experimental method with 25 rats as test animals divided into 5 treatment groups, namely 3 treatment groups (simple patch from 2.5% kayu jawa leaves extract, simple patch from 5% kayu jawa leaves extract, and simple patch from 10% kayu jawa leaves extract), 1 positive control group (simple patch from povidone iodine) and 1 negative control group (simple patch without kayu jawa leaves extract). The conclusions of the study was the administration of 5% Kayu Jawa leaves extract gave the best effect in accelerating wound healing.